Implications of the Second Amendment to Law Number 17 of 2014 on the Performance of Members of the House of Representatives in the Perspective of Fiqh Siyasah - Erik Yudistira; Siti Ngainnur Rohmah (JOURNAL of LEGAL RESEARCH, 2021)
Transparency in the legislative process is essential for the successful implementation of legislation that is in the public's best interests. As previously indicated, when one examines the problematic rules contained in this new iteration of the MD3 Law, one will find several articles that contribute to non-transparency in various actions carried out inside the DPR, particularly in the Baleg DPR. understand the legal rules contained in Law Number 17 of 2014 concerning MD3 that pertain to the performance of the DPR; in addition, understand the implications of the DPR's performance of the legislative function contained in Law Number 17 of 2014 concerning MD3 from the perspective of Siyasah Fiqh. A legal approach is taken in the research, which is done through normative legal research or library law research with a legal approach, in this case, research on legal products. The findings revealed that the legislative function of the DPR-RI as Ahlul Halli Wal Aqdi from the standpoint of fiqh siyasah increased from 16 (sixteen) bills in the 2016–2017 session year to 17 (seventeen) bills in the 2015–2016 session year, compared to the previous year. In comparison to the aim set for the 2017 Annual Priority National Legislation Program, which is 49 bills, this rise appears to be less substantial. According to Fiqh Siyasah, Ahlul Halli Wal Aqdi must prioritize policies that are beneficial to Islam and refrain from establishing laws that are in conflict with the Qur'an. Meanwhile, members of the DPR may amend rules that are in conflict with religious beliefs so long as the rules are state policies that are approved by a majority of its members.